An Analysis of Semiotic In Queen’s Song “Bohemian Rhapsody” - Syamsu T; Andi Asrifan; Andi Sadapotto; Emy Nur Rahmayani; suleha .; abdul Kahar (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
Analyzing data is an activity of thinking and recognizing data which is then described so that it becomes component signs. Regarding signs, in studying English several sciences need to be studied, one of which is semiotics. Semiotics is the study of signs contained in objects that have specific meanings. In this study the researcher wanted to analyze song from Band Queen, namely Bohemian Rhapsody,